FRI0128 Less than 5% of ethnic minority rheumatoid arthritis (RA) patients meet inclusion criteria for randomized controlled clinical trials (RCT). (23rd January 2014) - Kerr, G.; Yazici, Y.; Swearingen, C.; Luo, C.; Espinoza, L.; Sherrer, Y.; Treadwell, E.; Mosley-Williams, A.; Alamino Perez, R.; Dowell, S.; Godoy, A.; Paul, M.; et al.
Abstract : Background: RCT are the gold standard for therapeutic efficacy, yet many studies indicate most patients seen in routine clinical care do not meet inclusion criteria. 1 Apart from cultural challenges to the enrollment of ethnic minorities in clinical studies, decreased access and care, and late presentation in disease course may preclude inclusion in RA RCT. However, eligibility of ethnic minorities for RA RCT, to the best of our knowledge, has not been reported Objectives: To evaluate standard RCT inclusion criteria in a cohort of ethnic minority RA patients. Methods: Consented EMRAC patients were evaluated for the following standard, high disease activity, RCT inclusion criteria: swollen joints (28) >= 6, tender joints (28) >= 6, ESR >= 28, morning stiffness >= 45 min. We also evaluated the cohort for low disease activity, defined as swollen (28) <= 1, tender (28) <= 1, ESR <= 10, morning stiffness <= 15 min. Comparisons were made of each individual criteria, high versus low disease activity, and overall RCT eligibility by Race (Caucasian, African American) using Chi-square test. Results: 232 EMRAC patients were available for analysis, 158 African Americans, 74 Caucasians. The mean age was 63 years and the mean disease duration was 13.1 years. Only 4.4% African Americans (AA) and 4.1% of Caucasians met standard RCT inclusion criteria, despite only 3.8% AA and 8.1% Caucasians, respectively, meeting criteria for low disease activity. Approximaetely half of patients meeting RCT criteria received biologic therapy, while 30% had hypertension and none had coronary heart disease. The most stringent criterion was swollen joint count, with only 18.4% of AA and 14.9% of Caucasians meeting criteria, followed by tender joint count (24.1% AA and 31.1% Caucasians). 52.5% AA and 43.2% Caucasian patients, respectively, met ESR criteria, while 39.2 % of both AA and Caucasians met morning stiffness thresholds. Conclusions: In addition to reported socio-economic and cultural hurdles that preclude enrollment of ethnic minorities in RCT, African Americans, like their Caucasian counterparts, also fail to meet eligibility for RCT despite active disease. These data may suggest reconsideration of current entry criteria for RCT in all patients with RA. References: Sokka, T. J. Rheumatol, 2003 Disclosure of Interest: G. Kerr Grant/research support from: EMRAC receives support from Genentech, Pfizer, Bristol Myers Squibb, Y. Yazici: None Declared, C. Swearingen: None Declared, C. Luo: None Declared, L. Espinoza: None Declared, Y. Sherrer: None Declared, E. Treadwell: None Declared, A. Mosley-Williams: None Declared, R. Alamino Perez: None Declared, S. Dowell: None Declared, A. Godoy: None Declared, M. Paul: None Declared